2019
DOI: 10.3390/f10050438
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Impacts of Fuel Treatment Placement with Respect to Forest Cover Type on Potential Fire Behavior across a Mountainous Landscape

Abstract: Research Highlights: The impact of variation in fuels and fuel dynamics among forest cover types on the outcome of fuel treatments is poorly understood. This study investigated the potential effects of treatment placement with respect to cover type on the development of potential fire behavior over time for 48 km2 of forest in Colorado, USA. Our findings can inform the placement of fuel treatments in similar forests to maximize their effectiveness and longevity. Background and Objectives: Efficient placement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Moreover, tools that advance mechanistic connections of coupled fireatmospheric dynamics to ecological fire effects are years away. In the meantime, research grade models can be used to develop innovative training environments such as virtual reality simulations that game ignition patterns (Furman 2018) and assess fuel treatment effectiveness (Ex et al 2019). Just as flight simulators are required for pilots, use of such tools for prescribed burn boss training could become a standard supplemental experience to better align fire behavior with prescribed fire planning, implementation, and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, tools that advance mechanistic connections of coupled fireatmospheric dynamics to ecological fire effects are years away. In the meantime, research grade models can be used to develop innovative training environments such as virtual reality simulations that game ignition patterns (Furman 2018) and assess fuel treatment effectiveness (Ex et al 2019). Just as flight simulators are required for pilots, use of such tools for prescribed burn boss training could become a standard supplemental experience to better align fire behavior with prescribed fire planning, implementation, and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In ponderosa pine and dry mixed conifer forests, management goals for restoration typically emphasize structural changes to increase resistance and resilience to disturbances. Some of these objectives include (1) reducing overstory density, (2) increasing horizontal complexity, (3) maintaining tree size complexity, and (4) reducing the potential for regeneration by shade-tolerant species, such as Douglas-fir, that can act as ladder fuels and reduce treatment longevity [91]. Our results suggest that even with similar reductions in basal area, treatment prescriptions that differ in spatial pattern may differ markedly in their congruence with each of these goals, exhibiting important trade-offs among objectives related to tree density, structural complexity, and light environment.…”
Section: Discussionmentioning
confidence: 99%
“…Although there were only 16 studies in which beneficial wildfire metrics were measured and compared to a control scenario, in 80% of the cases (39 of 49 scenarios), the treatments resulted in higher values of beneficial fire. Putative reasons for cases where treatments failed to reduce overall/damaging wildfire or increase beneficial include the following: (1) treatments resulted in less damaging wildfire at the expense of more overall fire (Schmidt et al 2008;Sidman et al 2016;Halofsky et al 2017;Liang et al 2018;McCauley et al 2019;Stockdale et al 2019b); (2) treatments were geared primarily toward timber harvest, restoration, or habitat protection rather than fuel reduction (Roloff et al 2005;Merzenich et al 2003;Cassell 2018) ; (3) treatments were effective initially but resulted in changes in fuel structure through vegetation succession that increased burn susceptibility over the longer term (Loehman et al 2018;Ex et al 2019); (4) treated area was too small to have an effect under a given fire regime (Kim et al 2009;Syphard et al 2011b); or (5) stochastic variation of simulations with few replicates led to unexpected results (Jones et al 2008).…”
Section: Treated Vs Untreatedmentioning
confidence: 99%
“…They showed that optimizing fire threat reduction alone predictably led to the best outcomes from a wildfire protection perspective, or alternatively found ways to balance wildfire protection with other ecosystem services under given budget constraints (Hummel and Calkin 2005;Ager et al 2016;Bagdon et al 2016). Ex et al (2019) addressed a question that is applicable to many montane landscapes in western North America that contain a patchwork of cover types associated with different topographic settings. They asked whether it would be more effective to treat more mesic north-facing slopes dominated by Douglas fir versus more xeric south-facing slopes dominated by ponderosa pine, given a one-time treatment opportunity at the start of a 50-year simulation.…”
Section: Prioritizationmentioning
confidence: 99%